Using protein residue analysis and other methods to determine scraper function and bison influence at La Crosse locality sites in southwestern Wisconsin - McQuin, Michael; McQuin, Michael (My University, 2010)
A recurring question concerning Oneota archaeology at the La Crosse locality of southwestern Wisconsin is how bison scapulas are procured. More directly, do the scapulas and other bison skeletal elements found at La Crosse locality sites indicate seasonal hunting of bison, or simply the trading for scapulas to use as hoes? A second question often asked concerning this subject is whether or not the abundance of scrapers found at La Crosse locality sites indicates the processing of bison hides. This paper attempts to explore such questions through three methods. These methods include an adapted version of Binford's modified general utility index, scraper-to-point ratios, and protein residue analysis on lithic tools found at the Northern Engraving site (47Lc164), an Oneota site is La Crosse county, Wisconsin.
Keywords: Archaeology -- Methodology.; Oneota Indians (Great Plains) -- Implements -- Wisconsin -- La Crosse.; Archaeology -- Statistical methods.